2000
DOI: 10.1037/0278-7393.26.3.703
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a 40-Hz oscillatory short-term visual memory revealed by human reaction-time measurements.

Abstract: Four experiments show that presentation of a synchronous premask frame within a 40-Hz, flickering premask matrix primes subsequent detection of a Kanizsa-type square by generation of a 40-Hz prime. Reaction time (RT) priming effects indicated a 150-200-ms prime duration following premask display. Kite were also found to be sensitive to the phase relationship between offset of the premask display relative to the onset time of the target: Priming effects were maximal when the target was presented out of phase wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 42 publications
3
41
0
2
Order By: Relevance
“…A second set of studies has shown perception to be influenced directly by the timing of subthreshold stimuli. More specifically, these findings have shown that the coding of spatial grouping is expedited following the prior presentation of rapidly repeating premask elements in the same phase of a multi-element and multiphase presentation matrix (Elliott & Mu¨ller, 1998, 2000, 2001. In these studies, the premask elements, which were divided across a number of presentation phases, were presented repeatedly and at high frequency such that the precise temporal relations between the elements could not be determined by observers (Elliott & Mu¨ller, 1998, Experiment 2).…”
Section: Introductionmentioning
confidence: 90%
“…A second set of studies has shown perception to be influenced directly by the timing of subthreshold stimuli. More specifically, these findings have shown that the coding of spatial grouping is expedited following the prior presentation of rapidly repeating premask elements in the same phase of a multi-element and multiphase presentation matrix (Elliott & Mu¨ller, 1998, 2000, 2001. In these studies, the premask elements, which were divided across a number of presentation phases, were presented repeatedly and at high frequency such that the precise temporal relations between the elements could not be determined by observers (Elliott & Mu¨ller, 1998, Experiment 2).…”
Section: Introductionmentioning
confidence: 90%
“…One line of evidence relates to the subthreshold, oscillatory-priming effects reported by Elliott and colleagues (Elliott & Müller, 1998, 2000Kompass & Elliott, 2001). Prime responses exhibit a number of particular temporal characteristics: Primes persist for duration shorter than that of iconic memory but consistent with the persistence of a visible stimulus (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Prime responses exhibit a number of particular temporal characteristics: Primes persist for duration shorter than that of iconic memory but consistent with the persistence of a visible stimulus (i.e. <= 300 ms, see Coltheart, 1980), and are periodic, characterized by the frequency of priming-display presentations (the prime reaction time (RT) x premask-target ISI functions were periodic with a frequency of around 40 Hz, see Elliott & Müller, 2000). That prime persistence comes to be characterized by the frequency of prime-display presentation (the priming stimulus comprises one of four repeatedly presented but asynchronized image frames each presented at 10 Hz) has been taken as an indication that the prime is generated by mechanisms capable of coding global stimulus properties in interaction with relatively early visual-coding mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engel, Kreiter, König, & Singer, 1991;Kreiter & Singer, 1992). In a second line of evidence Elliott and colleagues (Elliott & Müller, 1998, 2000 have shown that a masked grouping embedded in a flickering display will prime detection of a subsequent grouping only if the masked grouping is embedded within 40 Hz flicker. Further examination of the temporal specificity of these effects was reported by Elliott and Müller (2004) who showed several specific bandpass characteristics located at 32 Hz, between 37 and 40 Hz and between 46 and 47 Hz.…”
Section: Introductionmentioning
confidence: 98%